Strategi Peningkatan Pembelian Wedding Package di Masa Pandemi Covid-19 pada CV. Legacy Bali Wedding, Denpasar - Luh Putu Citrawati (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2021)
In this reseach the analysis used is the marketing mix of 8P (Product, Price, place, Promotion, People, Process, Physical Evidence, and Productivity and Quality). And analyzed using SWOT analysis (Strengths, Weakness, Oppurtunities and Threats) in order to identify various factors systematically to formulate an appropriate marketing mix strategy carried out by Legacy Bali Wedding. Primary and secondary data obtained and analyzed using for marketing mix startegies namely SO (Strength and Oppurtunities), ST (Strengths and Threats), WO (Weaknesses and Oppurtunities), and WT (Weaknesses and Threats) strategies., so as to produce and appropriate conclusion and suggestion in knowing the Mrketing Mix Strategy to Improve Consumer Decisions in Wedding Purchases Pakcage at CV. Legacy Bali Wedding.